1984
DOI: 10.1148/radiology.152.3.6463252
|View full text |Cite
|
Sign up to set email alerts
|

Cervical disk herniation: CT demonstration after contrast enhancement.

Abstract: Two-millimeter-thick transverse axial CT scans were obtained at the 2, 3, or 4 cervical disk level in 25 patients with cervical radiculopathy. Scans were obtained before and after high dose (bolus/drip) intravenous administration of contrast medium. Clinical signs and symptoms were correlated with radiographic and surgical findings. Ventral epidural and intervertebral foraminal veins were consistently well visualized with this technique. Venous and dural enhancement provided better anatomic definition than did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…Epidural fibrosis has long been known to be associated with disk hemiations in the previously unoperated patient [2]. The epidural venous plexus has also shown consistent enhancement in the operated spine, a finding that has been used to advantage in the unoperated cervical spine by using contrast material with CT to increase the conspicuity of extradural disease [3]. …”
mentioning
confidence: 99%
“…Epidural fibrosis has long been known to be associated with disk hemiations in the previously unoperated patient [2]. The epidural venous plexus has also shown consistent enhancement in the operated spine, a finding that has been used to advantage in the unoperated cervical spine by using contrast material with CT to increase the conspicuity of extradural disease [3]. …”
mentioning
confidence: 99%
“…Our study examined the vertebral vein (VV) that emerged from the transverse foramen and opened into the brachiocephalic vein (BCV). As described in previous reports, the cervical VV emerges from the sixth cervical vertebra, joins the posterior external plexus, descends laterally, and opens as a single trunk at the root of the neck into the posterior aspect of the BCV near its origin (Batson, 1957;Greitz et al, 1962;Lockhart et al, 1965;Lanz and Wachsmuth, 1982;Russell et al, 1984). An accessory VV occasionally arises from a plexus formed around the VA by the VV, descends with the VV, emerges from the seventh cervical transverse foramen, and independently empties into the BCV (Lanz and Wachsmuth, 1982).…”
Section: Introductionmentioning
confidence: 79%
“…There have been numerous comprehensive anatomical and radiological studies published concerning the cervical vertebral venous system (Batson, 1957;Greitz et al, 1962;Lockhart et al, 1965;Lanz and Wachsmuth, 1982;Russell et al, 1984). The vertebral venous system consists of four intercommunicating divisions: the central or internal network consists of the vessels that surround the spinal dura mater within the spinal canal (epidural venous plexus): the vessels within the bone of the vertebrae themselves (basivertebral veins): the plexuses external to and surrounding the vertebral column (anterior and posterior external plexus): and the vertebral veins outside/inside to the transverse foramina (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The cervical vertebral vein is a U -or ringshaped structure surrounding the vertebral artery in the transverse process foramen of the upper cervical vertebrae [6]. The vertebral vein below the level of the sixth cervical vertebra is seen as a round opacification adjacent to the vertebral artery located anterolateral to the musculus longissimus colli on contrast-enhanced CT (Figs.…”
Section: Vertebral Veinsmentioning
confidence: 99%
“…Compared with the anterior epidural venous plexus, the posterior half is rarely seen. Russell et al [6] showed that visualization of the posterior displacement of the enhanced epidural veins provides excellent delineation of disk extrusion on contrast-enhanced CT.…”
Section: Internal Plexus (Epidural Venous Plexus)mentioning
confidence: 99%